(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The textile industry in India is vital to the economy of the country. It contributes to over six per cent of the gross domestic product of India and earns more than eighteen per cent of the total foreign exchange earnings of the country. The textile industry consists of three distinct sectors, viz., ginning, spinning and weaving.